Application of a Photoacoustic Tomography System: A Case Study on the Monitoring of Pig Tissue Decomposition - Oey, Lusiana Sandra; Mitrayana, Mitrayana; Wasono, Moh. Ali Joko (Makara Journal of Science, 2022)
Pig carcasses have been used in forensic research because they share several similarities to human cadaver, including decomposition. In several studies, the decomposition of pig’s cadaver for a certain time can be used as a model to determine the time of death of a human. This study was conducted to determine the relationship between the days of spoilage of pig tissue and the level of average sound intensity produced by the sample. Then, in this study, pig skeletal muscles were allowed to decay with a variation of 1–5 days. Afterward, these muscles were imaged using diode laser-based photoacoustic tomography. Results of the experiment show that the average acoustic intensity level from the first day until the fourth day has increased (78–92 a.u for young pig and 76–86 a.u for old pig) but decreased on the fifth day (88 a.u for young and 84 a.u for old pig). These results can improve forensic imaging because such results can be applied to determine the time of death of human by plotting the ratio of the average sound intensity level of the sample to the number of days of decomposition.